Cognitive network channel allocation method based on the queuing delay and game analysis - Jun LIU; Xiu-feng XIE (Tongxin xuebao)
A new dynamic spectrum allocation method for distributed cognitive radio networks was proposed.In the method,packet transmission success rate is chosen as the utility function,the transmission delay is resolved by the priority queuing model,and the user’s channel allocation strategy is achieved by distributed game.Compared with other algorithms,the policy iteration process is improved effectively,and a dynamic strategy adjustment step is adopted.Each network user dynamically adjust their channel choose strategy based on current perception of the remaining user’s strategy.The proposed algorithm lets channel selection strategy converge more quickly to equilibrium point,and effectively suppresses the policy shocks.The simulation results validate the proposed algorithm.